Hubungan Peran Perawat Sebagai Edukator Dengan Kepatuhan Diet Pasien DM Tipe II di Ruangan Emerald Rumah Sakit Kartika Kasih Kota Sukabumi - Nadia Nurdinilah; Erna Safariyah; Ernawati Hamidah (Pusat Riset dan Inovasi Nasional, 2024)
Diabetes mellitus (DM) in Indonesia ranks 7th out of 10 countries with a population of more than 10.8 million people in 2022. The feeling of boredom and boredom that appears in DM patients causes non-compliance with the diet they consume. Therefore, it is necessary to emphasize more on the role of nurses as educators. The purpose of this research is to determine the relationship between the role of nurses as educators and diet compliance in type II DM patients. This type of research is quantitative correlational, the number of 25 respondents used a Purposive Sampling technique, the instrument used was a questionnaire on the role of nurses with DM Diet, data analysis techniques using Univariate and Bivariate spearment-rank to test the statistical degree of relationship with a value of α=0.05. The research results were 19 respondents (76.0%) Almost all respondents stated that the role of nurses was good, based on Diet Compliance 15 respondents (60.0%) Some of the respondents stated that they were obedient, and there was a relationship between the Role of Nurses as Educators. With Diet Compliance in Type II Diabetes Mellitus Patients in the Emerald Room at Kartika Kasih Hospital, Sukabumi City with a value of ρ value = 0.076 > α = 0.05. It can be concluded that the importance of the role of nurses in providing education to patients and families regarding the dietary patterns of patients in hospital care as part of nursing care management.